(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the impact of art therapy implemented through visual arts tools on the process of social adaptation. The study analyzes how visual artistic activities contribute to the development of communication skills, emotional expression, and social interaction among students. Special attention is paid to the role of art therapy in reducing social anxiety, improving interpersonal relationships, and facilitating adaptation in educational environments. In addition, the pedagogical effectiveness of art-therapy-based methods applied in visual arts lessons is examined.